Acknowledging Documentary Filmmaking as not Only an Output but a Research Process: A Case for Quality Research Practice. (8th September 2020) - Fitzgerald, Angela; Lowe, Magnolia
Documentary films play an important role in how we see and position ourselves in the world. While traditionally viewed as a creative practice, documentary filmmaking has been transitioning into the academic world as a way to undertake and engage with research practices. Some question marks remain, however, over the nature of documentary filmmaking as a research method. This paper seeks to build a case for documentary as a research practice using Guba and Lincoln's quality criteria, which is typically employed to ensure the trustworthiness of collected data, as a frame for sense making. This case for research innovation also draws upon the first author's previous experiences with video ethnography and the second author's expertise as a documentary film maker. Their collaboration resulted in a longitudinal research project that foregrounded documentary practices as key to data gathering and sense making. This research project sought to understand the early career experiences of Australian graduate teachers from their perspective. Using this research project as a context, this paper unpacks how seven quality criteria can be explored and addressed using documentary filmmaking as method. This work highlights the possibilities and challenges inherent in innovating in the qualitative methodology space when considering the use of documentary filmmaking practices. It also adds meaningful and practical insights to a growing groundswell of voices that recognize documentary filmmaking as a viable and valuable research method.